Contribution of small ruminants to food security for Ethiopian smallholder farmers - Desta, Hiwot; Alemu, Biruk G.; Kinati, Wole; Mulema, Annet A.; Eerdewijk, Anouka van; Wieland, Barbara (Elsevier, 2020)
This study investigates how and to what extent arguments related to food security influence preference of livestock species for women and men. Data was collected in four regions of Ethiopia through 92 focus group discussions (FGD) in communities where small ruminant production is common, Using a gender sensitive study designs, 23 FGDs were held separately with men, women and youth (male and female), and through a household survey involving 217 male and 212 women. Qualitative analysis was conducted to extract reasons given to explain the importance of livestock. Reasons related to food security were mapped to the four dimensions underpinning food security—accessibility, availability, nutritional value and stability. All FGDs considered sheep the most important livestock species, followed by cattle, with women allocating higher scores to sheep than men. All four dimensions of food security came up in statements explaining the importance of species but with variations across species. Interestingly, food security related arguments were most prevalent for goats followed by poultry. Of reasons given by women concerning the importance of goats, 78 % were related to food security with all four dimensions represented, and 52 % for poultry with two dimensions (availability and nutritional value). Answers from men especially had a stronger focus on economic reasons directly linked to income generation. Nevertheless, 64 % of men’s arguments for goats were related to food security. For sheep however, women only scored higher for arguments related to availability. When investigating purpose of small ruminant production at household level through a household survey, the importance of small ruminants for food security were confirmed; however, gender differences were less apparent. Being able to sell animals at short notice was the main reason for keeping small ruminants for both women and men followed by meat and milk for home consumption. Women’s argument for prioritizing selling were accessibility. For men, key arguments for selling were related to availability. For meat and milk their nutritional value was an important argument. Comparing agroecologies, accessibility (selling) was ranked top in highland areas and nutritional value (milk) was most important in lowland areas. In conclusion, this study provides much needed evidence on how small ruminants contribute to different dimensions of food security and are promising entry points targeting women to improve food and nutritional security by providing adequate animal source foods in a household.